2021
DOI: 10.3390/antiox10111758
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Potentially Targets Epicardial Adipose Tissue to Reduce Cardiovascular Disease Risk in Patients with Metabolic Diseases: Oxidative Stress and Inflammation Emerge as Major Therapeutic Targets

Abstract: Excess epicardial adiposity, within a state of obesity and metabolic syndrome, is emerging as an important risk factor for the development of cardiovascular diseases (CVDs). Accordingly, increased epicardial fat thickness (EFT) implicates the exacerbation of pathological mechanisms involving oxidative stress and inflammation within the heart, which may accelerate the development of CVDs. This explains increased interest in targeting EFT reduction to attenuate the detrimental effects of oxidative stress and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 83 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…Metformin and insulin, which are commonly used antidiabetic therapies, have certainly prolonged the lives of patients with diabetes ( Joya-Galeana et al, 2011 ; Foretz et al, 2014 ; Bailey, 2017 ). Correspondingly, other effective interventions like physical exercise and caloric striction can be used to manage diabetes ( Nyawo et al, 2021 ; Shakoor et al, 2021 ; Mthembu et al, 2022 ), however only a few individuals can constantly adhere to such strenuous interventions. Besides lowering glucose or improving insulin sensitivity, it has become imperative to uncover therapies that can target the amelioration of both oxidative stress and inflammation, as the prime dysregulations implicated in the pathogenesis of diabetes ( Vikram et al, 2014 ; Mahlangu et al, 2020 ; Mokgalaboni et al, 2021b ).…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…Metformin and insulin, which are commonly used antidiabetic therapies, have certainly prolonged the lives of patients with diabetes ( Joya-Galeana et al, 2011 ; Foretz et al, 2014 ; Bailey, 2017 ). Correspondingly, other effective interventions like physical exercise and caloric striction can be used to manage diabetes ( Nyawo et al, 2021 ; Shakoor et al, 2021 ; Mthembu et al, 2022 ), however only a few individuals can constantly adhere to such strenuous interventions. Besides lowering glucose or improving insulin sensitivity, it has become imperative to uncover therapies that can target the amelioration of both oxidative stress and inflammation, as the prime dysregulations implicated in the pathogenesis of diabetes ( Vikram et al, 2014 ; Mahlangu et al, 2020 ; Mokgalaboni et al, 2021b ).…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…A recent study showed that bad childhood experience is associated with increased EAT in children with depression and reduced physical exercise ( 116 ). Studies have indicated that regular physical activity is an effective non-invasive strategy for reducing EAT that may provide beneficial effects on the cardiovascular system ( 113 , 117 , 118 ). Several studies showed that aerobic exercise decreases EAT thickness significantly in obese men ( 118 , 119 ).…”
Section: Therapeutic Options In Eatmentioning
confidence: 99%
“…In the past decade, four types of interventions have been proposed to reduce EAT volume, including exercise interventions, dietary interventions, bariatric surgery, and pharmaceutical interventions 129–134 (Figure 3). There have been a number of well‐designed tables summarizing related clinical studies in recent systematic reviews 134–142 …”
Section: Exploration Of Targeting Eat As a Therapeutic Strategymentioning
confidence: 99%
“…Numerous studies have investigated the impact of exercise on EAT amount 135–137 . A variety of exercise training protocols were evaluated in these studies, including aerobic exercise, high‐intensity exercise, and resistance exercise, and the length of programs varies from 3 to 24 weeks 133,138,143–149 .…”
Section: Exploration Of Targeting Eat As a Therapeutic Strategymentioning
confidence: 99%